Nivel del conocimiento del suministro de medicamentos en los estudiantes matriculados en el semestre 2013 - II de Farmacia y Bioquímica de la Universidad Nacional de Trujillo – 2013 - Cerna Alonzo, Katy Elizabeth (2014)
The present research work aims to determine the level of knowledge of drug supply in students enrolled in the 2013-II semester of Pharmacy and Biochemistry, National University of Trujillo. It was used as instrument to measure the knowledge a questionnaire of 21 questions with 2 sections, the first with general information such as age, sex and questions about attitude and the second with 21 knowledge questions, validated by assessing a panel of experts; was applied the questionnaire to 84 students in class schedule, for the evaluation of the questionnaire it was used a scale for measuring interval , by the formula ±δ; the data was analyzed using simple frequency tables of a input. The obtained results revealed that 47.62% of the students evaluated had a good level of knowledge on the regulation of the drug supply, but 44.05% and 8.33% of these student had a acceptable and low level respectively. While 85.71 % of the students had an acceptable level of knowledge of the stages of the supply of drugs, the 3.57% a good level and 10.71% a low level, finding the highest percentage the level good and low of knowledge in programming and acquisition stage with 58.33 % and 36.90 % respectively.